2004
DOI: 10.1128/aem.70.4.1944-1955.2004
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Phylogenetic Diversity of Sphingomonas Strains in Soils Contaminated with Polycyclic Aromatic Hydrocarbons

Abstract: Bacterial strains of the genus Sphingomonas are often isolated from contaminated soils for their ability to use polycyclic aromatic hydrocarbons (PAH) as the sole source of carbon and energy. The direct detection of Sphingomonas strains in contaminated soils, either indigenous or inoculated, is, as such, of interest for bioremediation purposes. In this study, a culture-independent PCR-based detection method using specific primers targeting the Sphingomonas 16S rRNA gene combined with denaturing gradient gel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
158
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(171 citation statements)
references
References 55 publications
8
158
1
4
Order By: Relevance
“…Several genera belonging to Acetobacteraceae have been linked with hydrocarbon degradation at moderately low pH levels (Hamamura et al, 2005;Rö ling et al, 2006). Sphingomonadaceae, Burkholderiaceae and Pseudomonadaceae are recognized for their extraordinary catabolic flexibility and are among the most common hydrocarbon degraders in a variety of soils (Leys et al, 2004;Stolz, 2009;Silby et al, 2011;Pérez-Pantoja et al, 2012); however, a thorough knowledge on pH optima of these groups is still lacking. Although these results provide clues about the pH preferences of these bacterial groups in the studied site, it remains to be shown whether they successfully degrade PAH or TPH compounds under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several genera belonging to Acetobacteraceae have been linked with hydrocarbon degradation at moderately low pH levels (Hamamura et al, 2005;Rö ling et al, 2006). Sphingomonadaceae, Burkholderiaceae and Pseudomonadaceae are recognized for their extraordinary catabolic flexibility and are among the most common hydrocarbon degraders in a variety of soils (Leys et al, 2004;Stolz, 2009;Silby et al, 2011;Pérez-Pantoja et al, 2012); however, a thorough knowledge on pH optima of these groups is still lacking. Although these results provide clues about the pH preferences of these bacterial groups in the studied site, it remains to be shown whether they successfully degrade PAH or TPH compounds under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, endophytic Burkholderiaceae species have been detected in several crops (Sun et al, 2008). Similarly, members of the Sphingomonadaceae family are widespread in different types of soils, sediments, and pelagic aquatic environments, and are known for their ability to utilize a wide variety of carbon sources; several are in fact renowned degraders of recalcitrant (xenobiotic) molecules (Leys et al, 2004). Additionally, some sphingomonads were also found to play important roles in the mycorrhizosphere (Boersma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These isolated strains, PHPY and SK, are proposed to be new members of Sphingomonadaceae and Rhodobacteraceae, respectively. Several reports have shown the important role of bacteria in Sphingomonadaceae for PAH degradation in soils 16,31,32 , mangrove sediments 33 , and deep subsurface sediments 34 . This study, in accordance with previous reports 35 , also found that sphingomonads with PAH degradation ability can be isolated from seawater, indicating that sphingomonads are found in a wide variety of environments and might play a key role in the degradation of PAHs in various environments, including the marine environment.…”
Section: Discussionmentioning
confidence: 99%